2022
DOI: 10.1039/d2dt02986c
|View full text |Cite
|
Sign up to set email alerts
|

Alloying nickel and cobalt with iron on ZSM-5 for tuning competitive hydrogenation reactions for selective one-pot conversion of furfural to gamma-valerolactone

Abstract: One-pot conversion of furfural, a biomass-derived platform chemical, to gamma-valerolactone (GVL), a fuel additive and green solvent, involves multiple steps of hydrogenation. Among these reactions, the deep hydrogenation of the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…20,47 On one hand, with the increase of doping Cu content in the bimetallic samples, the peak intensity gradually increased. As stated above, the easily reducible Cu could overflow hydrogen to nearby Ni phy and accelerate its reduction; 48 the scattered breaking bonds of Ni-O-Si thus lead to the exposure and increase of the proximal acidic sites. 27,45 On the other hand, the L acid intensity is decreased with the increase of reduction temperature, which is consistent with the acidity amount variation in NH 3 -TPD.…”
Section: Dalton Transactions Papermentioning
confidence: 96%
“…20,47 On one hand, with the increase of doping Cu content in the bimetallic samples, the peak intensity gradually increased. As stated above, the easily reducible Cu could overflow hydrogen to nearby Ni phy and accelerate its reduction; 48 the scattered breaking bonds of Ni-O-Si thus lead to the exposure and increase of the proximal acidic sites. 27,45 On the other hand, the L acid intensity is decreased with the increase of reduction temperature, which is consistent with the acidity amount variation in NH 3 -TPD.…”
Section: Dalton Transactions Papermentioning
confidence: 96%
“…The addition of a second metal has been reported to favor the hydrogen spillover phenomenon, thus promoting the catalyst's ability to adsorb and activate hydrogen, which contributes to its elevated catalytic efficacy in the hydrodeoxygenation of guaiacol. 76 3.3. S, C, N, P Catalysts.…”
Section: Transition Metal Catalystsmentioning
confidence: 99%
“…Furthermore, Guo et al found that there is a significant correlation between the Al species with Ni and Co, indicating that both Ni and Co can take up electrons from the Al species in the carrier. The addition of a second metal has been reported to favor the hydrogen spillover phenomenon, thus promoting the catalyst’s ability to adsorb and activate hydrogen, which contributes to its elevated catalytic efficacy in the hydrodeoxygenation of guaiacol …”
Section: Effects Of Water On the Performance Of Biomass Hydrodeoxygen...mentioning
confidence: 99%
“…33−37 Moreover, H-ZSM-5-based catalysts are reported to show promising activity for the conversion of FUR and FA to levulinic acid/esters and gamma-valerolactone. 35,38 Recently, Zhao et al reported a comparative study on the application of various solid acids for the conversion of FA to alkyl levulinates wherein H-ZSM-5-based catalysts showed superior catalytic performance. 36 Nonetheless, other zeolite-based catalysts, e.g., H-ZSM-12, are also known to have good catalytic activity for the esterification of levulinic acid.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The study suggests a proficient route for support modification wherein optionally various other solid acids/bases or metals can be used as per the requirement. In the present study, H-ZSM-5 is chosen as an acidic component to prepare the acido-basic composite due to its tunable acidity and its proven activity for alcoholysis reaction including alcoholysis of FA to EL. Moreover, H-ZSM-5-based catalysts are reported to show promising activity for the conversion of FUR and FA to levulinic acid/esters and gamma-valerolactone. , Recently, Zhao et al reported a comparative study on the application of various solid acids for the conversion of FA to alkyl levulinates wherein H-ZSM-5-based catalysts showed superior catalytic performance . Nonetheless, other zeolite-based catalysts, e.g., H-ZSM-12, are also known to have good catalytic activity for the esterification of levulinic acid .…”
Section: Introductionmentioning
confidence: 99%